Signatures of selection for bonamiosis resistance in European flat oyster (Ostrea edulis): New genomic tools for breeding programs and management of natural resources. (5th July 2019) - Vera, Manuel; Pardo, Belén G.; Cao, Asunción; Vilas, Román; Fernández, Carlos; Blanco, Andrés; Gutierrez, Alejandro P.; Bean, Tim P.; Houston, Ross D.; Villalba, Antonio; Martínez, Paulino
Abstract: The European flat oyster ( Ostrea edulis ) is a highly appreciated mollusk with an important aquaculture production throughout the 20th century, in addition to playing an important role on coastal ecosystems. Overexploitation of natural beds, habitat degradation, introduction of non‐native species, and epidemic outbreaks have severely affected this important resource, particularly, the protozoan parasite Bonamia ostreae, which is the main concern affecting its production and conservation. In order to identify genomic regions and markers potentially associated with bonamiosis resistance, six oyster beds distributed throughout the European Atlantic coast were sampled. Three of them have been exposed to this parasite since the early 1980s and showed some degree of innate resistance (long‐term affected group, LTA), while the other three were free of B .  ostreae at least until sampling date (naïve group, NV). A total of 14, 065 SNPs were analyzed, including 37 markers from candidate genes and 14, 028 from a medium‐density SNP array. Gene diversity was similar between LTA and NV groups suggesting no genetic erosion due to long‐term exposure to the parasite, and three population clusters were detected using the whole dataset. Tests for divergent selection between NV and LTA groups detected the presence of a very consistent set of 22 markers, located within a putative single genomic region, which suggests the presence of a major quantitative trait locus associated with B. ostreae resistance. Moreover, 324 outlier loci associated with factors other than bonamiosis were identified allowing fully discrimination of all the oyster beds. A practical tool which included the 84 highest discriminative markers for tracing O. edulis populations was developed and tested with empirical data. Results reported herein could assist the production of stocks with improved resistance to bonamiosis and facilitate the management of oyster beds for recovery production and ecosystem services provided by this species.